#PositiveEnergy Douyin: constructing "playful patriotism" in a Chinese short-video application. Issue 1 (2nd January 2021) - Chen, Xu; Valdovinos Kaye, D. Bondy; Zeng, Jing
Abstract : In Chinese political discourse, "positive energy" ( zheng nengliang ) is a popular expression that has embodied mainstream political ideology in China since 2012. This term has also become prominent on Douyin, a prominent Chinese short-video platform. By June 2018, over 500 Chinese governmental accounts on Douyin had promoted positive energy in videos, and the content was viewed over 1.6 billion times. Douyin even created a separate trending section, Positive Energy, for videos that promoted the dominant state ideology. This study argues that the Positive Energy feature on Douyin is significant. The Chinese government has accused and even permanently shut down several digital platforms for spreading "vulgarity" as the antithesis of positive energy. Using the app walkthrough method and a content analysis of over 800 videos collected from the Positive Energy section of Douyin, this study explores how Douyin promotes the Chinese state's political agenda by promoting a new form of playful patriotism online.